Pre‐existing influenza‐specific nasal IgA or nasal viral infection does not affect live attenuated influenza vaccine immunogenicity in children. (13th January 2021) - Cole, M. E.; Kundu, R.; Abdulla, A. F.; Andrews, N.; Hoschler, K.; Southern, J.; Jackson, D.; Miller, E.; Zambon, M.; Turner, P. J.; Tregoning, J. S.
Summary: The United Kingdom has a national immunization programme which includes annual influenza vaccination in school‐aged children, using live attenuated influenza vaccine (LAIV). LAIV is given annually, and it is unclear whether repeat administration can affect immunogenicity. Because LAIV is delivered intranasally, pre‐existing local antibody might be important. In this study, we analysed banked samples from a study performed during the 2017/18 influenza season to investigate the role of pre‐existing influenza‐specific nasal immunoglobulin (Ig)A in children aged 6–14 years. Nasopharyngeal swabs were collected prior to LAIV immunization to measure pre‐existing IgA levels and test for concurrent upper respiratory tract viral infections (URTI). Oral fluid samples were taken at baseline and 21–28 days after LAIV to measure IgG as a surrogate of immunogenicity. Antibody levels at baseline were compared with a pre‐existing data set of LAIV shedding from the same individuals, measured by reverse transcription–polymerase chain reaction. There was detectable nasal IgA specific to all four strains in the vaccine at baseline. However, baseline nasal IgA did not correlate with the fold change in IgG response to the vaccine. Baseline nasal IgA also did not have an impact upon whether vaccine virus RNA was detectable after immunization. There was no difference in fold change of antibody between individuals with and without an URTI at the time of immunization. Overall, we observed no effect of pre‐existing influenza‐specific nasal antibody levels on immunogenicity, supporting annual immunization with LAIV in children. Abstract : Live attenuated influenza vaccine (LAIV) needs to enter cells to induce an immune response, because of this pre‐existing immunity to strains in the virus might dampen the immunogenicity. We tested whether local antibodies in the nose, the site of immunisation, affected immunogenicity. There was no link between pre‐existing nasal antibody or concurrent viral infection on LAIV immunogenicity.